Biological Effects of BET Inhibition by OTX015 (MK-8628) and JQ1 in NPM1-Mutated (NPM1c) Acute Myeloid Leukemia (AML) - Hanane Djamai (MDPI AG, 2021)
BET inhibitors (BETi) including OTX015 (MK-8628) and JQ1 demonstrated antileukemic activity including NPM1c AML cells. Nevertheless, the biological consequences of BETi in NPM1c AML were not fully investigated. Even if of better prognosis AML patients with NPM1c may relapse and treatment remains difficult. Differentiation-based therapy by all trans retinoic acid (ATRA) combined with arsenic trioxide (ATO) demonstrated activity in NPM1c AML. We found that BETi, similar to ATO + ATRA, induced differentiation and apoptosis which was TP53 independent in the NPM1c cell line OCI-AML3 and primary cells. Furthermore, BETi induced proteasome-dependent degradation of NPM1c. BETi degraded NPM1c in the cytosol while BRD4 is degraded in the nucleus which suggests that restoration of the NPM1/BRD4 equilibrium in the nucleus of NPM1c cells is essential for the efficacy of BETi. While ATO + ATRA had significant biological activity in NPM1c IMS-M2 cell line, those cells were resistant to BETi. Gene profiling revealed that IMS-M2 cells probably resist to BETi by upregulation of LSC pathways independently of the downregulation of a core BET-responsive transcriptional program. ATO + ATRA downregulated a NPM1c specific HOX gene signature while anti-leukemic effects of BETi appear HOX gene independent. Our preclinical results encourage clinical testing of BETi in NPM1c AML patients.